Developing science literacy in the 21st century - Croce, Keri-Anne; Firestone, Jonah (Emerald Publishing Limited : Information Age Publishing, Inc., 2020)
"The development of science literacy has the potential to have an enormous impact on real world outcomes. Specifically, developing science literacy may persuade individuals to act. Because of the enormous responsibilities associated with persuading individuals to act, we hope that the audiences for this book will include scientists, science journalists, sociologists, anthropologists, communication specialists, political leaders, media outlets, educational institutions, and individual science content consumers. The chapters in this book describe a definition of science literacy that draws on the emotional, cognitive, and social. The authors of the chapters in this book strive to help prepare individuals to read, write, and speak science in a continuously evolving information landscape. In order to meet these objectives, the chapters examine both qualitative and quantitative research. It is within these frameworks that we can begin to address science literacy in the 21st century"-- Provided by publisher.
Keywords: Science -- Study and teaching.; Communication in science.; Science -- Social aspects.; Science -- Study & Teaching.; Impact of science and technology on society.; Science: general issues.; Teaching of a specific subject.; elektronické knihy; electronic books